INVESTIGATION OF THE PERFORMANCE OF SINGLE AND MULTI-CELL STACKS OF PEMFC - -, Indriyati; Irmawati, Yuyun; Subhan, Achmad (Teknologi Indonesia, 2015)
The performance of single, 3-cell, and 5-cell stacks of PEMFC have been experimentally investigated. Emphasiswas placed on the effect of different operating condition including hydrogen/oxygen flow rate and pressure on thePEMFC performance through analysis of polarization curves. The results showed that flow rate slightly affected theperformance of single-cell PEMFC at higher current densities whereas no significant differences were observed atlower current densities. Similar curve patterns were obtained when testing the single and 3-cell PEMFC stacks withvariation of backpressure. Increasing backpressure gives positive effect on the stack performance due to improvingthe reaction at the electrodes. However, this behavior did not occur on 5-cell PEMFC stack the performance of which decreased as the backpressure increased from 5 to 10 psi due to increasing water production in the cathode. In this study, the highest operational (at voltage of 0.6 V) current density of 85.6 mA/cm2 was obtained from 3-cell stack with flow rate of H2/O2 and backpressure 800/1,000 ml/min and 10 psi, respectively. This good performanceis more evident when the 3-cell stack was evaluated over a quite long operation time. After decreasing gradually at the first 50 min operation, the performance of 3-cell stack of PEMFC remained stable up to 200 min, while it fluctuated in 5-cell stack due to poor water management. This study confirms that the performance of PEMFC stack is highly influenced by the number of cell and operating condition, and the performance of PEMFC stack is not linear as function of number of cell.